An assessment of the viability of alternatives to biodiesel transport fuels - Kächele, Rebecca (2021)
This work presents an economic feasibility study of using algae and biochar burial strategies to offset carbon emission from the use of conventional fossil-derived transport fuels. The economic feasibility is quantified on the basis that the final price of the decarbonised fossil-derived diesel should be lower or equal to the price of biodiesel which is deemed to be the next best alternative. The extra costs associated with the carbon capture/offset via algae and biochar burial are estimated for the most typical scenarios using the economic models developed as part of this work. In addition, High Dimensional Model Representation based global sensitivity analyses are performed in order to quantify the influence of key model parameters on the overall costs. It was found that using algae burial to offset carbon emissions is not viable for principle reasons such as the amount of water required and the burial of phosphate as well as more than doubling the current diesel price. This price is mainly due to the high costs of pumping dilute algae slurry underground. The biochar burial approach, on the other hand, was found to be much more economically viable as it only increases the conventional diesel price by a small amount. This comparably low price is due to the revenue generated from selling the electricity produced from the pyrolysis by-products. In addition, the global sensitivity analysis revealed that the overall costs were the most sensitive to the wood price, as the wood feedstock may either be an income or an expenditure.